THE ROLE OF MASDAR PATTERNS IN EXPRESSING MEANING IN ARABIC (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the phenomenon of triliteral Arabic verbs possessing multiple masdar (verbal noun) forms. The study examines the principal factors that produce masdar variation namely, dialectal differences among Arab tribes and semantic specialization and demonstrates through Qurʼanic evidence how different masdars of the same verb can diverge in meaning and serve specialized contextual functions. The masdars ُكْفر, كفران, and كفور derived from the verb كفر, as well as صوم and صيام, are analyzed for their semantic properties and Qurʼanic distribution. The article further demonstrates that certain Arabic morphological patterns possess inherent semantic values a property illustrated through the fiʿalah pattern and that changing a masdar’s pattern can alter its meaning.
Keywords: Arabic language; masdar; morphological pattern; triliteral verb; semantic specialization; Qurʼan; dialect; morphology; fiʿalah pattern; semantic differentiation.